Leadership Through Competing and Caring - Jain, P. K.; Singh, I. P.; Jain, Minakshi (Prabandhan: Indian Journal of Management, 2008)
For India, growth is an imperative. The country aspires to be a major economic power house by the end of the century’s first quarter. To achieve that, India needs to accelerate and maintain an economic growth rate that is beyond the 6-7% per annum that has been seen since the early 1990s. To achieve this India needs people with vigor, honesty and all the more goodness in mind and heart. If India should be lead, it should be by people with serene and sincere minds and hearts. As the recession has set in world wide, only those economies will survive the onslaught of severe recession which are capable of providing effective and charismatic leadership. Strong and capable leaders are the most critical resource for a country’s development. A nation especially a developing one, needs leaders not just in the business area but in all walks of life, especially political and social. Once of the biggest challenges confronting India in this time of transition is able leadership that can envision the big picture in an increasingly global economy. What then are the guiding principles that a leader, in the current Indian context, must use to effectively steer his organization and the wider community around it, to success?